Determinants affecting the level of awareness towards bankruptcy risks among youth in private sector at Lorong Dungun, Damansara,Kuala Lumpur / Nabila Syuhada Mohamed Azami - Mohamed Azami, Nabila Syuhada (Faculty of Business and Management, 2014)
The research reported in this paper is the basic research on “Level of Awareness towards Bankruptcy Risk among Youth in Private Sector at Lorong Dungun, Damansara, Kuala Lumpur. Nowadays, bankruptcy is one of the leading factors that cause youth to be affected with financial risk. Here, the awareness toward factors influencing bankruptcy risk is very important. The main objective of this research are (1) to determine the Level of Awareness towards Bankruptcy Risk among Youth in Private Sector at Lorong Dungun, Damansara, Kuala Lumpur (2) to examine the relationship between Financial Literacy, Financial Attitude and Financial Motivation with the Level of Awareness towards Bankruptcy Risk and (3) to determine the most influential factor that contributes to the Level of Awareness towards Bankruptcy Risks. 100 questionnaires were distributed to employees in private sector in Lorong Dungun, Damansara, Kuala Lumpur. The researcher applied a convenience sampling as the sampling technique. Throughout this research, the Level of Awareness is recorded as in a high level group of awareness with 3.9820 amount of mean. Generally, there are weak and significant relationship between independent variable (Financial Literacy, Financial Attitude and Financial Motivation) and dependent variable (Level of Awareness). The most influential factor is Financial Literacy with coefficient of 0.363. This coefficient shows that for every unit increase in Financial Literacy a 0.363 unit increase in the level of awareness toward factors influencing Bankruptcy Risk among Youth in Private Sector at Lorong Dungun, Damansara, Kuala Lumpur. The result shows a positive relationship between Financial Literacy and Level of Awareness towards Bankruptcy Risk towards Bankruptcy Risks among Youth in Private Sector in Lorong Dungun, Damansara, Kuala Lumpur. In conclusion, all the Research Objectives drawn for the research have been achieved. Research Objective 1 has been achieved with High Level of Awareness towards Bankruptcy Risks among Youth in Private Sector in Damansara, Kuala Lumpur. The Second Objective; to determine the Level of Awareness among Dependent Variable and Dependent Variable, also has been achieved with weak correlation between the Independent Variables and positive relationship between all the Independent Variables with the Dependent Variables. For Research Objective 3, the most influential factors influencing the Level of Awareness has been determined with Financial Literacy becomes the most influential factors.